Physiological and physical performance changes during a 20-day winter military training course and its subsequent 10-day recovery period - Ojanen, Tommi; Pihlainen, Kai; Vaara, Jani P.; Kyröläinen, Heikki (International Journal of Circumpolar Health, 2023)
The present study investigated physiological, mental and physical performance changes during a 20-day winter military training course and the following 10-day recovery period. Fifty-eight (age 19 ± 1 years, height 182 ± 6 cm, body mass 78.5 ± 7.2 kg) male soldiers volunteered. Body compo sition, serum biomarker levels and performance tests were measured four times during the study. In addition, questionnaires were collected daily for subjective stress and rate of perceived exertion. The course induced significant declines in body (−3.9%, p < 0.05) and fat mass (−31.6%, p < 0.05) as well as in all assessed physical performance variables (−9.2 - −20.2%, p < 0.05), testosterone (−73.7%, p < 0.001) and IGF-1 concentrations (−43.6%, p < 0.001). At the same time, the sex hormone-binding globulin, creatine kinase, and C-reactive protein values increased significantly (46.3–1952.7%, p < 0.05). After the 10-day recovery period, the body composition and hormonal values returned to the baseline (p < 0.05), as did some physical performance variables, such as 2 min sit-ups and the evacuation test (p < 0.05). However, explosive force production in the upper and lower bodies remained unrecovered. The 20-day winter military training caused significant physiological and mental stress, as well as a drastic decline in physical performance even for highly physically fit soldiers, and the 10-day recovery period did not establish full recovery.